Zinc Supplementation Promotes a Th1 Response and Improves Clinical Symptoms in Fewer Hours in Children With Pneumonia Younger Than 5 Years Old. A Randomized Controlled Clinical Trial - Acevedo-Murillo, Jorge Alberto; García León, Miguel Leonardo; Firo-Reyes, Verónica; Santiago-Cordova, Jorge Luis; Gonzalez-Rodriguez, Alejandra Pamela; Wong-Chew, Rosa María (Frontiers in Pediatrics, 2019)
Background: Pneumonia caused 704,000 deaths in children younger than 5 years in 2015. Zinc is an important micronutrient due to its role in immune function. Since 2004, WHO recommends zinc supplementation for children with diarrhea to shorten the duration and decrease severity. Zinc supplementation for children with pneumonia is controversial. Methods: A randomized controlled clinical trial was conducted, and 103 children 1 month to 5 years old with pneumonia were included. Zinc or placebo was given during hospitalization. Clinical symptoms were recorded, and a blood draw was obtained to determine serum zinc levels, lymphoproliferation, and cytokines at hospitalization and at discharge of the patient; a nasal wash was obtained to detect viral or bacterial pathogens by multiplex RT-PCR. Results: Zinc supplementation improved in fewer hours the clinical status (76 ± 7 vs. 105 ± 8, p = 0.01), the respiratory rate (37 ± 6 vs. 57 ± 7, p = 0.04), and the oxygen saturation (53 ± 7 vs. 87 ± 9, p = 0.007) compared to the placebo group. An increase in IFNγ and IL-2 after treatment in the zinc group was observed. Conclusions: Zinc supplementation improved some clinical symptoms in children with pneumonia in fewer hours and induced a cellular immune response. Clinical Trial Registration: The trial was retrospectively registered in ClinicalTrials.gov, identifier NCT03690583, URL https://clinicaltrials.gov/ct2/show/NCT03690583?term=zinc+children&cond=Pneumonia&draw=2&rank=1.